The invasive plant Mikania micrantha affects the soil foodweb and plant-soil nutrient contents in orchards. (December 2019) - Sun, Feng; Ou, Qiaojing; Yu, Hanxia; Li, Na; Peng, Changlian
Abstract: Microbial-microfaunal interactions play important roles in nutrient release and plant nutrient acquisition. However, the extent of their effects is sensitive to plant species identity, particularly among invasive plants, and the difference in effects can change the proportional abundances of soil functional groups, and subsequently change plant-soil element contents. Although the effects of invasive plants on soil microorganisms have been a widespread focus of ecological research, interspecific interactions with fauna are rarely considered in studies of plant invasion. We explored the potential of soil nematodes to mediate microbial responses to an invasive plant ( Mikania micrantha ) and a native plant ( Persicaria chinensis ) in South China, where ecological niches are extremely sensitive to exotic species because of anthropogenic degradation of the native vegetation. Rhizosphere soil samples were collected from three different habitats highly invaded by M. micrantha, and the abundance and community composition of the nematode and microbial communities were examined. A microcosm experiment was also conducted to test whether nematode feeding significantly affected specific bacteria-mediated ecological processes, such as potassium release in the soil. The results of the correlation analysis, structural equation modeling and laboratory microcosm experiments consistently indicated that the abundance of bacterivores was positively correlated with bacterial biomass, including that of potassium-solubilizing bacteria. In microcosms, the most dominant bacterivore, Eucephalobus, significantly increased potassium release by stimulating the colonies and activity of potassium-solubilizing bacteria. Meanwhile, M. micrantha had higher potassium stocks in plant tissues, especially in the roots, than did P. chinensis . These findings clearly suggest that invasive plants may enhance microbial-microfaunal interactions that in turn stimulate nutrient release. Highlights: Soils under the invasive species have an enhanced bacteria-based energy channel. Soils under the invasive species have weaken root-based energy channel. Bacterivore-bacterial interaction was greater in invasive species soils than native. Invasive species roots had higher level of potassium stocks than of non-invasive.